43.0k views
5 votes
Question 9 of 20 :

Select the best answer for the question.
9. –2x(–3x 2y)(2y) = ?

A. 12x3y2
B. –3xy2
C. 3xy2
D. –12x3y2

User Jhoepken
by
4.7k points

2 Answers

3 votes
I think it’s d I’m not sure
User Chen Fisher
by
4.9k points
5 votes

For this case we must find the product of the following expression:


-2x * (- 3x^2y) * (2y) =

We take into account that:


- * - = +

To multiply powers of the same base, the same base is placed and the exponents are added:


6x^(1 + 2)y * 2y =\\6x ^ 3 * 2y ^ {1 + 1} =\\12x ^ 3y ^ 2

ANswer:


12x ^ 3y ^ 2

Option A

User Dehalion
by
4.8k points